Screen time evaluation, association with obesity, and cardiorespiratory fitness among children aged 10–12 years - Agre, Sharayu; Agrawal, Ronika; Alirajpurwala, Arwa (Indian Journal of Child Health, 2019)
Background: Screen time (ST) is defined as the viewing or use of anything with a screen including TV, DVDs, video games, and computers. They reduce time for outdoor activities resulting in less physical work. Thus, it is necessary to establish a relationship between ST and obesity and its association with cardiorespiratory illnesses. Objective: The objective of this study was to determine the correlation of ST with obesity and cardiorespiratory fitness (VO2 max) among children aged 10–12 years. Materials and Methods: Body mass index (BMI), waist–hip ratio (WHR), and VO2 max of each child were calculated. The children were also given a questionnaire consisting of 45 activities categorized into moderate- and vigorous-intensity physical activities and leisure activities which they usually perform in the entire week. Thus, total duration for all activities performed in a day was summed. Data were analyzed for correlation. Results: The average age of students was 11.09 years. Average BMI of males was 16.52±3.67 kg/m2. Average BMI for females was 17.12±2.46 kg/m2. Average VO2 max for students was 35.83 ml/kg/min. ST for students was ranging from 40 min to 190 min. Positive correlation between ST and BMI of children was r=0.66 which suggests as ST increases BMI increases. Similar trend was seen with WHR and VO2 max, suggesting that as ST increases endurance decreases and risk for cardiorespiratory disease increases. Conclusion: Increased ST in children increases the chances of obesity and reduces the level of cardiorespiratory fitness.